2012
DOI: 10.1007/s10008-012-1678-7
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of activated carbon-based symmetric supercapacitors in Li2SO4 and KOH aqueous electrolytes

Abstract: In this work, we have prepared activated carbon (AC)-based symmetric supercapacitor (SC) using Li 2 SO 4 aqueous electrolyte instead of H 2 SO 4 and KOH and obtained a device with an improved cell voltage window (CVW) of 0−1.6 V from 0 to 1.0 V. The SC using KOH electrolyte is also fabricated for comparison. The electrochemical characteristics of SCs such as cyclic voltammetry (CV), galvanostatic charge-discharge, electrochemical impedance spectroscopy (EIS) and cycle stability are investigated systematically.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(36 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…The potential window of the carbon/Na 2 SO 4 system is roughly twice that in the traditional KOH and H 2 SO 4 electrolytes [17,[69][70][71]. Such enhancement has been attributed either to the high overpotential for dihydrogen evolution at the negative electrode [79] or to the strong solvation of cations and anions [19].…”
Section: Extension Of Stability Window In Neutral Aqueous Electrolytesmentioning
confidence: 86%
See 3 more Smart Citations
“…The potential window of the carbon/Na 2 SO 4 system is roughly twice that in the traditional KOH and H 2 SO 4 electrolytes [17,[69][70][71]. Such enhancement has been attributed either to the high overpotential for dihydrogen evolution at the negative electrode [79] or to the strong solvation of cations and anions [19].…”
Section: Extension Of Stability Window In Neutral Aqueous Electrolytesmentioning
confidence: 86%
“…Despite all the aforementioned advantages of aqueous electrolyte, a major disadvantage of water, when considering Equations 8.6 and 8.7, is its low thermodynamic stability and consequently low reachable cell potential of 1.23 V [68]. In practice, it is even less than 1.00 V in symmetric carbon-based SCs with H 2 SO 4 and KOH aqueous electrolytes [17,[69][70][71][72], whereas AC/AC capacitors in organic medium can be cycled at 2.7-2.8 V [73]. Hence, most of the industrial EDLCs available in the market are based on organic electrolyte, for example, tetraethylammonium tetrafluoroborate in AN.…”
Section: Electrolytes For Electrical Double-layer Capacitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although, the high concentration of salt solution can enlarge the potential window due to the increase of over potential to H + reduction or O 2 oxidation reaction. Sun et al [13] reported the enlargement of oxidation potential of EDLC up to 1.6 V in 1 M Li 2 SO 4 solution. Therefore, in our work, the operational potential in Li 2 SO 4 and Na 2 SO 4 solution was cut at 1 V and the concentration was 1 M to avoid the corrosion of stainless steel current collector and the decomposition of electrolyte at its surface.…”
Section: Resultsmentioning
confidence: 99%